Effect of crude oil shock load on anoxic-aerobic sequential moving bed reactors during petroleum refinery wastewater treatment. (20th December 2021) - Mallick, Subrat Kumar; Chakraborty, Saswati
Abstract: Concentrations of pollutants are suddenly increased (shock loads) in the lab-scale bioreactors to examine their stability against sudden change in feeding conditions. In the present study, sudden elevated loads of crude oil were supplied to an anoxic (A1)-aerobic (A2) sequential reactor system, as studies involving series reactors for shock analysis are scarce. The system was previously engaged in the treatment of petroleum refinery wastewater at influent crude oil of 300 mg/L along with phenol, sulfide, nitrate-N and ammonia-N. Influent crude oil was suddenly increased to 600 mg/L and 900 mg/L during first (shock 1) and second (shock 2) shock loadings, respectively, at two different times of operation. An immediate increase in the effluent organics and a decrease in efficiency was observed after each shock. The shock toxicity caused death of microbes and decrease (1–4%) in biomass concentration. Hence, biomass activity reduced, and the pollutants degradation declined by 40–50%. Nitrogen production in A1 decreased which confirmed lesser nitrate utilization during shock. Both the reactors recovered to their original stature after the withdrawal of shock 1. Shock 2 had a permanent effect on A1 as its efficiency decreased from 33% to 11% even after withdrawal of the shock. The combined A1-A2 system successfully tolerated the shock loads, and more than 99% removals of organics, sulfide, and nitrate was achieved after resumed normalcy. Graphical abstract: Image 1 Highlights: Efficacy of the system declined with sudden increase in crude oil concentrations. Biomass, CFU, activity and SRT decreased at sudden elevated influent crude oil. Reactors recovered totally after crude oil was reduced from 600 mg/L to 300 mg/L. Anoxic reactor was harmed when crude oil was elevated from 300 mg/L to 900 mg/L. Overall anoxic-aerobic system was stable after withdrawal of elevated crude oil.